DNA sequencing using biotinylated dideoxynucleotides and mass spectrometry - Edwards, John R. (Oxford University Press, 2001)
Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MS) has been explored widely for DNA sequencing. The major requirement for this method is that the DNA sequencing fragments must be free from alkaline and alkaline earth salts as well as other contaminants for accurately measuring the masses of the DNA fragments. We report here the development of a novel MS DNA sequencing method that generates Sanger-sequencing fragments in one tube using biotinylated dideoxynucleotides. The DNA sequencing fragments that carry a biotin at the 3′-end are made free from salts and other components in the sequencing reaction by capture with streptavidin-coated magnetic beads. Only correctly terminated biotinylated DNA fragments are subsequently released and loaded onto a mass spectrometer to obtain accurate DNA sequencing data. Compared with gel electrophoresis-based sequencing systems, MS produces a very high resolution of DNA-sequencing fragments, fast separation on microsecond time scales, and completely eliminates the compressions associated with gel electrophoresis. The high resolution of MS allows accurate mutation and heterozygote detection. This optimized solid-phase DNA-sequencing chemistry plus future improvements in detector sensitivity for large DNA fragments in MS instrumentation will further improve MS for DNA sequencing.